New Geophysical Data About the Pacific Margin (West Antarctica) Magnetic Anomaly Sources and Origin - Soloviev, V.D.; Bakhmutov, V.G.; Korchagin, I.N.; Yegorova, T.P. (Український антарктичний журнал, 2018)
During the seasonal work in the Ukrainian Antarctic expeditions (1997—2012), a significant amount of geological and geophysical studies were carried out. The main objective of the study is to obtain new data on the distribution of deep heterogeneities in the structures of the region. It’s allowed to construct the geophysical models and to discuss the existing ideas about the stages of formation and evolution tectonic structures of the West Antarctica near the Antarctic Peninsula (AP). New geophysical models of the Earth's crust were used to study the possible nature of the Pacific Coast magnetic anomaly (PMA) near the AP. Під час проведення сезонних робіт в українських антарктичних експедиціях (1997—2012 рр.) був виконаний значний обсяг геолого-геофізичних досліджень з метою отримання нових даних про розподіл глибинних неоднорідностей в структурах регіону, що дозволило побудувати комплексні геофізичні моделі та доповнити наявні уявлення про етапи формування та еволюції тектонічних структур Західної Антарктики поблизу Антарктичного півострова (AП).